Rational investing : the subtleties of asset management - LANGLOIS, HUGUES (Columbia Business School Publishing, 2017)
Many investors believe that success in investing is either luck or clairvoyance. In Rational Investing, finance professor Hugues Langlois and asset manager Jacques Lussier present the current state of asset management and clarify the conundrum of luck versus skill. The core of Rational Investing is a framework for smart investing built around three performance drivers: balancing exposure to risk factors, efficiently diversifying bad luck, and taking advantage of relative mispricings in financial markets. With clear examples from model multi-asset-class portfolios, Langlois and Lussier show how to implement performance drivers like institutional investors with access to extensive resources, as well as nonprofessional investors who are constrained to small-scale transactions. There are few investment products, whether traditional or alternative, discretionary or systematic, fundamental or quantitative, whose performance cannot be analyzed through this framework. Langlois and Lussier illuminate the structure of financial markets and the mechanics of sustainable investing so any investor can become a rational player, from the nonprofessional investor with a basic knowledge of statistics all the way to seasoned investment professionals wishing to challenge their understanding of the asset management industry.